Limb and sex-related differences in knee muscle co-contraction exist 3 months after anterior cruciate ligament reconstruction - Alfayyaadh, A.; Neal, K.; Williams, J. R.; Khandha, A.; Manal, K.; Snyder-Mackler, L.; Buchanan, T. S. (Journal of Electromyography and Kinesiology, 2022)
Interlimb and sex-based differences in gait mechanics and neuromuscular control are common after anterior cruciate ligament reconstruction (ACLR). Following ACLR, individuals typically exhibit elevated co-contraction of knee muscles, which may accelerate knee osteoarthritis (OA) onset. While directed (medial/lateral) co-contractions influence tibiofemoral loading in healthy people, it is unknown if directed co-contractions are present early after ACLR and if they differ across limbs and sexes. The purpose of this study was to compare directed co-contraction indices (CCIs) of knee muscles in both limbs between men and women after ACLR. Forty-five participants (27 men) completed overground walking at a self-selected speed 3 months after ACLR during which quadriceps, hamstrings, and gastrocnemii muscle activities were collected bilaterally using surface electromyography. CCIs of six muscle pairs were calculated during the weight acceptance interval. The CCIs of the vastus lateralis/biceps femoris muscle pair (lateral musculature) was greater in the involved limb (vs uninvolved; p = 0.02). Compared to men, women exhibited greater CCIs in the vastus medialis/lateral gastrocnemius and vastus lateralis/lateral gastrocnemius muscle pairs (p < 0.01 and p = 0.01, respectively). Limb- and sex-based differences in knee muscle co-contractions are detectable 3 months after ACLR and may be responsible for altered gait mechanics.